Similar Outcomes for Contact Aspiration and Stent Retriever Use According to the Admission Clot Burden Score in ASTER. Issue 7 (July 2018) - Zhu, François; Lapergue, Bertrand; Kyheng, Maéva; Blanc, Raphael; Labreuche, Julien; Ben Machaa, Malek; Duhamel, Alain; Marnat, Gautier; Saleme, Suzana; Costalat, Vincent; Bracard, Serge; Richard, Sébastien; et al.
Abstract : Background and Purpose—: The clot burden score (CBS) at admission reliably evaluates the thrombus burden in acute ischemic stroke patients with anterior circulation large vessel occlusion. Mechanical thrombectomy has been diversified, especially with contact aspiration technique, and its efficiency with respect to the thrombus burden is not known. We compared reperfusion, adverse events, neurological recovery, and 90-day functional outcome of stent retriever use versus contact aspiration according to the admission CBS. Methods—: This is a post hoc analysis of the ASTER (Contact Aspiration Versus Stent Retriever for Successful Revascularization) randomized trial. The primary outcome was successful reperfusion after all procedures, defined as modified Thrombolysis in Cerebral Infarction scores 2b/3. Secondary outcomes were 90-day functional outcome, assessed with the modified Rankin Scale. Safety outcomes included 90-day mortality and any intracerebral hemorrhage. Results—: A total of 231 randomized patients were included in this study: 114 patients had a CBS of 0 to 6 and 117 a CBS ≥7 at admission. Successful reperfusion at procedure end was achieved more frequently in patients with CBS ≥7 (88.9%) than patients with a CBS 0 to 6 (81.6%; fully adjusted risk ratio, 1.09; 95% confidence interval, 1.01–1.28). Favorable outcome (modified Rankin Scale score, 0–2) at 90 days was achieved in significantly more patients with CBS ≥7 (61.9%) than in patients with CBS 0 to 6 (41.8%; fully adjusted risk ratio, 1.19; 95% confidence interval, 1.02–1.40). No outcome differences of first-line mechanical thrombectomy strategy (aspiration versus stent) on any angiographic or clinical outcomes were observed between the 2 groups. We also found no evidence of interaction between first-line mechanical thrombectomy strategy and CBS groups regarding safety. Conclusions—: First-line mechanical thrombectomy with contact aspiration compared with stent retriever did not result in an increased successful reperfusion rate in acute ischemic stroke patients with large vessel occlusion of the anterior circulation according to the admission CBS. The latter, however, seems to be a reliable prognostic indicator of angiographic and clinical outcome.